Antihypertensive Efficacy of Fixed Combination of Amlodipine and Ramipril in Patients with Arterial Hypertension and Very High Cardiovascular Risk - O. Yu. Korennova; S. P. Podolnaya; E. P. Prihodko; E. A. Turusheva; S. N. Starinskaya; I. A. Вratishko; I. V. Druk (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To evaluate the antihypertensive efficacy and tolerability of a fixed combination of amlodipine and ramipril in hypertensive patients with very high cardiovascular risk. Material and methods. A retrospective cohort study of real clinical practice of prescribing antihypertensive drugs according to 255 medical records of outpatient hypertensive patients with a history of acute coronary syndrome (ACS) and coronary artery stenting was performed in the first part. An open observational study was performed in the second part. 69 people older than 18 years with a history of ACS and coronary artery stenting, without reaching the target blood pressure (BP) level while using free combinations of antihypertensive drugs and with indications for a fixed combination of ramipril and amlodipine were included into the study. Analysis of self-monitoring of BP, office BP, daily BP monitoring (ABPM) and patients’ adherence to treatment (Morisky-Green test) initially, after 4 and after 12 weeks of taking the fixed combination of ramipril and amlodipine was performed to assess the clinical efficacy of the studied drug. Results. It was found that 42.0% of patients did not follow the recommendations for regular intake of antihypertensive drugs. So, hypertension of all patients regarded as false-refractory, which was the basis for the prescription of the fixed combination of ramipril and amlodipine in accordance with clinical guidelines for the diagnosis and treatment of hypertension. After 4 weeks of therapy, there was significant decrease in office BP with the achievement and preservation of the target level by the 12th week, normalization to the 12th week of day and night BP variability in 54.9% of patients. 78.0% of patients followed medical recommendations for regular administration of antihypertensive drugs, none of the patients had adverse events. Conclusion. The use of fixed combinations of drugs, in particular, amlodipine and ramipril as a part of multicomponent therapy in hypertensive patients with very high cardiovascular risk, led to the achievement of target BP by the 4th week of therapy and stable preservation of antihypertensive effect in 12 weeks of treatment as well as gradual normalization of day and night BP variability in more than half of patients. Fixed combination of ramipril and amlodipine allowed to improve adherence of patients to cardiovascular diseases.